Direct ring fluorination of 3-substituted 5-(1,3-dioxane) acetal isoxazoles: application to the formal synthesis of a bioactive fluorinated isoxazole - Bacheley, Lucas; Guillamot, Gérard; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie (Comptes Rendus. Chimie)
The access to a novel variety of 4-fluorinated isoxazoles bearing an aryl or alkyl group at the C-3 position and an acetal fragment at the C-5 position has been achieved through a direct fluorination using N-fluorobenzenesulfonimide (NFSI) with yields up to 75%. This method was transposed to gram-scale and has been applied to the formal synthesis of a bioactive compound that increases CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) activity.